Dinamika dan Prospek Kebangkitan Militer Jepang - HERI ALFIAN (Politeia: Jurnal Ilmu Politik, 2010)
The dynamics of Japan military after World War II (WWI) are very interesting topic to be discussed because there are always two opposite argument about it. First, some people think that Japan is “not normal” state because since 1945 he has no military forces like other state. On the contrary, some people believed that Japan had been developing his military forces since 1951. Actually, those arguments are true, for the facts that in some point Japan military is not like ordinary one because it just for defense and mostly for non combatant and humanitarian tasks when it send abroad, but it is also very true that Japan military is military as in common term for the facts that they equipped with sophisticated weapons. This article will show us the Japan military facts and his strategy in developing it, which is doing in a very smart way that make some people still think that he is not normal.Keywords: Defense strategy, International politics, International relations